Wykorzystanie nowych technologii w orientacji przestrzennej osób z niepełnosprawnością wzroku - Miler-Zdanowska, Kamila (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The fast development of electronic and information technologies makes them becoming ever more present in the lives of the blind and visually impaired people. The aim of this article is to present modes of mobility of people with visual impairment, with particular focus on new technologies. The article contains the classification and characteristics of electronic aids used in spatial orientation and mobility for blind people. It also presents the benefits and difficulties of using these types of new technologies. The article presents research projects related to the construction and testing of new technical solutions in Poland.